Power quality in power systems and electrical machines - Fuchs, Ewald F.
Power Quality of power systems affects all connected electrical and electronic equipment. Power Quality is a measure of deviations in voltage and frequency of the particular supply system. In recent years, there has been a considerable increase in nonlinear loads; in particular distributed loads, such as computers, TV monitors and lighting. These draw harmonic currents which, when distorted, have detrimental effects including interference, loss of reliability, increased operating costs, equipment overheating, motor failures, capacitor failure and inaccurate power metering. This subject is pertinent to engineers involved with electric power systems, electronic equipment, computers and manufacturing equipment. This book shows readers to understand the causes and effects of power quality problems such as non-sinusoidal wave shapes, voltage outages, losses due to poor power quality, origins of single-time events such as voltage dips, voltage reductions, and outages, along with techniques to mitigate these problems. . Provides theoretical and practical insight into power quality problems of machines and systems . Problems/solutions at the end of each chapter dealing with practical applications . Includes application examples including SPICE, Mathematica, and MATLAB examples.